2011
DOI: 10.1002/hc.20740
|View full text |Cite
|
Sign up to set email alerts
|

Generation of pyrrolo[2,1‐a]isoquinoline derivatives from N‐ylides: Synthetic control and structural characterization

Abstract: New pyrrolo [2,1-a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…With other solvents and bases, the compounds 13 were obtained together with their corresponding dihydroderivatives 17. [34][35][36]47,50,54,55 Scheme 3. Synthesis of hybrid structures 13a-h.…”
Section: Reactions Of Bromides 7ab With Alkynesmentioning
confidence: 99%
See 1 more Smart Citation
“…With other solvents and bases, the compounds 13 were obtained together with their corresponding dihydroderivatives 17. [34][35][36]47,50,54,55 Scheme 3. Synthesis of hybrid structures 13a-h.…”
Section: Reactions Of Bromides 7ab With Alkynesmentioning
confidence: 99%
“…33 The most versatile method of synthesis of pyrroloazines is the 1,3-dipolar cycloaddition reaction between heteroaromatic N-ylides and acetylenic dipolarophiles. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] Herein we report the generation of sydnone-N-ylides as bis (1,3-dipoles) and their reactivity in the 1,3-dipolar cycloaddition reaction with acetylenic dipolarophiles. 1,3-Dipolar cycloaddition reaction of sydnone-N-ylides, as model bis (1,3-dipoles), with acetylenic dipolarophiles in 1,2-epoxybutane under reflux gave exclusively pyrroloazines containing a sydnone moiety that resulted by preferred reaction of the N-ylide 1,3-dipole with the acetylenic dipolarophiles.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these scaffolds were synthesized through the combination of MCR and one-pot synthesis. Literature search indicated that [3+2] cycloadditioninitiated method has also been used for the synthesis of hexahydropyrrolo[2,1-a]isoquinolines by employing stable 1,3-dilpolars generated from amino esters [15,40] or isoquinolines [41][42][43][44][45][46][47][48][49]. We like to report in this paper our effort on the synthesis of pyrrolidinedione-fused hexahydropyrrolo[2,1a]isoquinolines via sequential 1,3-dipolar cycloaddition, N-allylation, and intramolecular Heck cyclization reactions (Scheme 2, K).…”
Section: Scheme 1: [3+2] Cycloaddition With Amino Esters or Amino Acidsmentioning
confidence: 99%
“…Many of these scaffolds were synthesized through the combination of MCR and one-pot synthesis. A literature search indicated that a [3 + 2] cycloaddition-initiated method has also been used for the synthesis of hexahydropyrrolo[2,1-a]isoquinolines by employing stable 1,3-dilpolar compounds generated from amino esters [15,40] or isoquinolines [41][42][43][44][45][46][47][48][49]. We like to report in this paper our effort on the synthesis of pyrrolidinedione-fused hexahydropyrrolo[2,1-a]isoquinolines via sequential 1,3-dipolar cycloaddition, N-allylation, and intramolecular Heck cyclization reactions [50][51][52][53][54] (Scheme 2, K).…”
Section: Introductionmentioning
confidence: 99%